(untitled) (Journal of Social Sciences Review, 2023)
The Covid-19 pandemic has had a profound impact on the mental health and well-being of individuals around the world, including special children. In Pakistan, the pandemic has exacerbated existing financial and home-bound challenges faced by special children and their families. This qualitative study aimed to examine the psychological effects of the Covid-19 pandemic on special children in Pakistan and the ways in which financial and home-bound challenges have impacted their mental health. In-depth interviews and observation were used to gather data from participants. The findings revealed that the pandemic has resulted in increased stress and anxiety among special children, as well as decreased access to support and resources. The study highlights the importance of addressing the unique needs of special children and their families during times of crisis and provides insights into the strategies and support that can be implemented to mitigate the negative impacts of financial and home-bound challenges on their mental health. The results of this study contribute to the ongoing conversation about the impact of the pandemic on vulnerable populations and the need for targeted support during crisis situations.